Pull-out tests with CFRP laminates applied according to the ETS/NSM technique - Silva, C. A. N. da (2018)
The retrofitting technique of Near-Surface Mounted (NSM) fiber-reinforced polymer (FRP) strips is receiving more attention recently due to many advantages over the externally bonded technique (EBR). However, in some situation is necessary to increase flexural and shear simultaneous. Therefore, to overcome this drawback, a hybrid strengthening technique that combines the advantages of NSM technique and Embedded Through Section (ETS) technique, is proposed by using an innovative CFRP laminate with rectangular shape in the NSM part and circular shape in the ETS. In order to evaluate the efficiency of the strengthening system, this paper presents the results of a series of pull-out tests using the innovative laminate to quantify the influence of the angle and embedded length. Using the results of this experimental program and developing a numerical strategy, an analytical bond stress–slip relationship was obtained.